Peltoperlopsis mengmanensis sp. nov., the second species of Peltoperlopsis (Plecoptera: Peltoperlidae) from China - Chen, Zhi-Teng (Zootaxa, 2019)
A new species of the peltoperlid genus Peltoperlopsis Illies, 1966, Peltoperlopsis mengmanensis sp. nov. from Yunnan Province of southwestern China is described and illustrated. Males of the new species are characterized by tergum 10 with a U-shaped, apically incurved epiproctal sclerite, vesicle with an elliptical base and a subtriangular apex, cercal segments 11–12 each with a single moderately enlarged spine, and by aedeagus asymmetrical and bilobed. This is the second species of Peltoperlopsis reported from China.